Governing the Frontiers in the Ottoman Empire - Koç, Gülseren Duman, author.
1 online resource (325 pages)
Keywords: Based on many previously unused sources from Ottoman and British archives, Governing the Frontiers in the Ottoman Empire offers a micro-history to understand the nineteenth century Ottoman reforms on the eastern frontiers. By examining the administrative, military and fiscal transformation of Muş, a multi-ethnic, multi-religious sub-province in the Ottoman East, it shows how the reforms were not top-down and were shaped according to local particularities. The book also provides a story of the notables, tribes and peasants of a frontier region. Focusing on the relations between state-notables, notables-tribes, notables-peasants and finally tribes-peasants, the book shows both the causes of contention and collaborations between the parties.